2019
DOI: 10.1111/cas.14094
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 production mediated by the IRE1‐XBP1 pathway confers radioresistance in human papillomavirus‐negative oropharyngeal carcinoma

Abstract: Endoplasmic reticulum stress (ERS) plays a key role in the pathogenesis and development of tumors and protects tumor cells from radiation damage and drug‐induced stress. We previously demonstrated that EGFR confers radioresistance in human papillomavirus (HPV)‐negative human oropharyngeal carcinoma by activating ERS signaling through PERK and IRE1α. In addition, PERK confers radioresistance by activating the inflammatory cytokine NF‐κB. However, the effect of IRE1 on radiosensitivity has not yet been fully elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Consistently, Esra A Akbay et al identified a correlation between EGFR pathway activation and a signature of immunosuppression manifested by decreasing CTLs and increasing markers of T-cell exhaustion [ 30 ]. The transcription factor JUN was reported to activate the transcription of the promoters of several key UPR effectors, such as XBP1 and ATF4, to inhibit tumour cell apoptosis [ 45 , 46 ]. The hallmark of the exhausted subgroup, SERPINE1, induced by TGF-β in the microenvironment, may act as a target to reverse the exhausted immune response [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Esra A Akbay et al identified a correlation between EGFR pathway activation and a signature of immunosuppression manifested by decreasing CTLs and increasing markers of T-cell exhaustion [ 30 ]. The transcription factor JUN was reported to activate the transcription of the promoters of several key UPR effectors, such as XBP1 and ATF4, to inhibit tumour cell apoptosis [ 45 , 46 ]. The hallmark of the exhausted subgroup, SERPINE1, induced by TGF-β in the microenvironment, may act as a target to reverse the exhausted immune response [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic roles of XBP1 in CRC and other types of cancer have been reported in numerous studies; the activation of the IRE1/XBP1 pathway induced cell proliferation and invasion in CRC 3, whereby XBP1 was demonstrated to promote with poor prognosis (24); in breast cancer, the expression levels of XBP1s in the nucleus were correlated with shorter survival (25); whereas in ovarian cancer, the IRE1/XBP1 signaling pathway controlled T-cell functions, thus, mediating ER stress or targeting the IRE1/XBP1 pathway may restore the antitumor ability of T-cells (26). In addition, XBP1 positively regulated the cytolytic activity of human natural killer cells against leukemia cells (27); in hepatocellular carcinoma, the IRE1/XBP1 pathway controlled the expression of interleukin-6 (IL-6) and promoted hepatocarcinoma progression (28); and in oropharyngeal carcinoma without papillomavirus, the IRE1/XBP1 pathway induced resistance to radiotherapy by mediating IL-6 production (29). Thus, the transcription factor XBP1 may be a potential target to mediate tumor immunology and block cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…IRE1 is another principal sensor of ERS pathway, and its overexpression in HPV-negative OPCC patients treated with RT has been correlated with poor outcomes. IRE1 promotes IL-6 activation, enhancing X-ray-induced DNA DSB and cell apoptosis ( 112 ). Another mechanism that activates ERS signaling is the activation of EGFR conferring RR in OSCC.…”
Section: Endoplasmic Reticulum Adaptations To Radiationmentioning
confidence: 99%